Tourism as a source of taxation - the portuguese case - Rodrigues, Carlos (2020)
The phenomenon of world tourism has been growing worldwide and with it, all the economic evolution is supported by the multiple activities that support it. This study aims to understand how tourism in Portugal generates tax revenues that contribute to obtaining income for the annual budgets of the Portuguese state (J.J. Gomes Canotilho & Vital Moreira, 2007 p. 1088). The methodology applied to this analysis focuses only on two taxes and is exclusively supported by statistical data from highly credible institutions in Portugal. Thus, we can identify it as a mixed methodology (qualitative and quantitative), using research, analysis, and interpretation of scientific data.